Retinal Capillary Plexus Pattern and Density from Fovea to Periphery Measured in Healthy Eyes with Swept-Source Optical Coherence Tomography Angiography - Lavia, Carlo; Mecê, Pedro; Nassisi, Marco; Bonnin, Sophie; Marie-Louise, Jennifer; Couturier, Aude; Erginay, Ali; Tadayoni, Ramin; Gaudric, Alain (Scientific reports, 2020)
Optical coherence tomography angiography is evolving towards wider fields of view. As single widefield acquisitions have a lower resolution, preventing an accurate segmentation of vascular plexuses in the periphery, we examined the retinal vascularisation from the macula to the periphery in all retinal quadrants, using 3 × 3-mm volume scans, to obtain montages with sufficient image resolution up to 11 mm from the foveal centre. Images were qualitatively and quantitatively analysed, using C- and B-scan approaches to calculate the capillary density (CD) and the interplexus distance (IPD). Three vascular plexuses ( i.e ., superficial vascular plexus: SVP, intermediate capillary plexus: ICP, and deep capillary plexus: DCP) were observed up to the mid-periphery in all sectors. The CD of the SVP decreased from about 5 mm of eccentricity, along with ganglion cell density decrease. The CD of the ICP progressively decreased from the fovea towards the periphery, along with the retinal thinning and then vanished from 8 to 9 mm of eccentricity, becoming undetectable beyond. This ICP disappearance resulted in an increased IPD between the SVP and the DCP in an area known to be frequently affected by capillary drop-out in diabetic retinopathy. The DCP only showed a slightly decreased CD towards the retinal periphery.